2020
DOI: 10.1111/obr.13107
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and all‐cause mortality in patients with percutaneous coronary intervention: A dose–response meta‐analysis of obesity paradox

Abstract: The association between body mass index (BMI) and mortality of patients with percutaneous coronary intervention (PCI) is still controversial. We hope to explore whether the 'obesity paradox' really exists through this dose-response meta-analysis. PubMed, Embase and Cochrane databases were systematically searched for eligible studies up to April 2020. The random-effects restricted cubic spline models were used to evaluate the potential non-linear relationship between BMI and all-cause mortality of patients unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 53 publications
(84 reference statements)
2
13
1
Order By: Relevance
“…Obesity categories were associated with higher mortality risk in patients aged 18–45 years; however, underweight status was the predominant risk factor in the sample overall, accounted for by its salience in patients over 65 years old. Although obesity is recognised as a risk factor for cardiovascular diseases, 20 no associations were found with any BMI category and circulatory disease mortality in our sample; instead, associations, where present, were with respiratory disease mortality (for morbid obesity) and external-cause mortality (for overweight and obese status). The ‘obesity paradox’ describes the phenomenon that patients with an increasing BMI have a paradoxical decrease in mortality.…”
Section: Discussioncontrasting
confidence: 88%
“…Obesity categories were associated with higher mortality risk in patients aged 18–45 years; however, underweight status was the predominant risk factor in the sample overall, accounted for by its salience in patients over 65 years old. Although obesity is recognised as a risk factor for cardiovascular diseases, 20 no associations were found with any BMI category and circulatory disease mortality in our sample; instead, associations, where present, were with respiratory disease mortality (for morbid obesity) and external-cause mortality (for overweight and obese status). The ‘obesity paradox’ describes the phenomenon that patients with an increasing BMI have a paradoxical decrease in mortality.…”
Section: Discussioncontrasting
confidence: 88%
“…The body mass index (BMI) is widely accepted as a good indication of general adiposity, and a number of epidemiological studies have demonstrated that obesity, as measured by BMI, is a substantial risk factor for a variety of long-term illnesses and death (1,2). The link between BMI and mortality, on the other hand, has sparked a lot of debate, since epidemiological studies have discovered numerous forms of U-shaped, J-shaped, and linear relationships between BMI and mortality (3)(4)(5)(6)(7)(8). In several studies, being overweight, for example, was linked to an increased risk of mortality (9), while others found that overweight persons had the lowest death rate and that mortality increased with decreased BMI (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…According to the 2017 Global Nutrition Report, 2 billion adults were obese or overweight worldwide and about one in five patients in ICU was obese (5). In recent years, some studies have shown that obesity can reduce mortality in critically ill patients (5)(6)(7), such as those with chronic heart disease, chronic renal insufficiency, and sepsis, this phenomenon is termed obesity paradox (8)(9)(10)(11); Yet whether this phenomenon exists in ARDS is still controversial (12)(13)(14)(15)(16)(17)(18)(19)(20). Most of the previous studies were conducted with a limited sample size, and ARDS as defined by the Berlin standard was rarely applied.…”
Section: Introductionmentioning
confidence: 99%